Regional Effects of a Cluster-oriented policy measure. The Case of the InnoRegio program in Germany - Thomas Brenner; Carsten Emmrich; Charlotte Schlump (Philipps-University Marburg, Department of Geography, 2013)
This paper examines regional effects of the InnoRegio program, which was conducted by the German Federal Ministry of Education and Research. The InnoRegio program has been a new tool of innovation policy with the aim to improve innovativeness in East Germany on the basis of prosperous regional networks. Besides the direct support of networks and innovation activities, the program was meant to trigger the regional development in East Germany. While existing studies examine whether the development of networks or cluster was successful, this paper focuses on the investigation of regional economic development. Using regional data, especially on employment and patents, we examine whether the involved industries have developed better in supported regions than in other (East) German regions. Developments are investigated for a time span including years before, during and after the policy measure. We find some positive effects in the regional development that can be assigned to the InnoRegio program.
Keywords: C22; O12; O25; O33; R11; R28; 330; cluster policy; InnoRegio program; cluster; networks; region; employment; innovation; policy evaluation